Distinct phenotypes of new transmembrane-domain neuregulin 1 mutant mice and the rescue effects of valproate on the observed schizophrenia-related cognitive deficits - Pei, Ju-Chun; Liu, Chih-Min; Lai, Wen-Sung (Frontiers in Behavioral Neuroscience, 2014)
Accumulating evidence suggests that neuregulin 1 (NRG1) might be involved in the neurodevelopment, neural plasticity, GABAergic neurotransmission and pathogenesis of schizophrenia. NRG1 is abundantly expressed in the hippocampus, and emerging studies have begun to reveal the link between NRG1 signaling and cognitive deficits in schizophrenic patients. Because the transmembrane domain of NRG1 is vital for both forward and reverse signaling cascades, new Nrg1-deficient mice that carry a truncation of the transmembrane domain of the Nrg1 gene were characterized and used in this study to test a NRG1 loss-of-function hypothesis for schizophrenia. Both male and female Nrg1 heterozygous mutant mice and their wild-type littermates were used in a series of 4 experiments to characterize the impact of Nrg1 on behavioral phenotypes and to determine the importance of Nrg1 in the regulation of hippocampal neuromorphology and local GABAergic interneurons. First, a comprehensive battery of behavioral tasks indicated that male Nrg1-deficient mice exhibited significant impairments in cognitive functions. Second, pharmacological challenges were conducted and revealed that Nrg1 haploinsufficiency altered GABAergic activity in males. Third, although no genotype-specific neuromorphological alterations were found in the hippocampal CA1 pyramidal neurons, significant reductions in the hippocampal expressions of GAD67 and parvalbumin were revealed in the Nrg1-deficient males. Fourth, chronic treatment with valproate rescued the observed behavioral deficits and hippocampal GAD67 reduction in Nrg1-deficient males. Collectively, these results indicate the potential therapeutic effect of valproate and the importance of Nrg1 in the regulation of cognitive functions and hippocampal GABAergic interneurons, especially in males.